2010
DOI: 10.1007/s00224-010-9263-x
|View full text |Cite
|
Sign up to set email alerts
|

Randomness on Computable Probability Spaces—A Dynamical Point of View

Abstract: Abstract. We extend the notion of randomness (in the version introduced by Schnorr) to computable Probability Spaces and compare it to a dynamical notion of randomness: typicality. Roughly, a point is typical for some dynamic, if it follows the statistical behavior of the system (Birkhoff's pointwise ergodic theorem). We prove that a point is Schnorr random if and only if it is typical for every mixing computable dynamics. To prove the result we develop some tools for the theory of computable probability space… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
59
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(60 citation statements)
references
References 14 publications
1
59
0
Order By: Relevance
“…In [7], a characterization of Schnorr randomness in terms of dynamical typicalness was given. Here we state a slightly improved version, obtained using a result from [1] (see also [8]) which concerns the computability of the rate of convergence of ergodic averages.…”
Section: Introductionmentioning
confidence: 99%
“…In [7], a characterization of Schnorr randomness in terms of dynamical typicalness was given. Here we state a slightly improved version, obtained using a result from [1] (see also [8]) which concerns the computability of the rate of convergence of ergodic averages.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, [9] showed that in classical chaotic dynamics, typicality corresponds exactly to Schnorr randomness; this means that a chaotic system may produce a computable sequence of bits provided the initial point is suitable chosen, but this event has probability zero (the set of initial points can be infinite).…”
Section: Introductionmentioning
confidence: 99%
“…This has been inspired by Kučera's classic result characterising MartinLöf randomness in the Cantor space. We reformulate Kučera's result using the general terminology of [4]. Definition 2.…”
mentioning
confidence: 99%
“…2 Here we use the notion of a computable probability space of Gács, Hoyrup and Rojas [4], although all reasonable definitions of this concept are equivalent. For completeness, we recall the definition here.…”
mentioning
confidence: 99%
See 1 more Smart Citation